Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11420-009-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pulmonary Embolism in the Postoperative Orthopedic Patient Using Spiral CT Scans

Abstract: Orthopedic surgery is associated with a significant risk of postoperative pulmonary embolism (PE) and/or deep vein thrombosis (DVT). This study was performed to compare the clinical presentations of a suspected versus a documented PE/DVT and to determine the actual incidence of PE/DVT in the post-operative orthopedic patient in whom CT was ordered. All 695 patients at our institution who had a postoperative spiral CT to rule out PE/DVT from March 2004 to February 2006 were evaluated and information regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…29 Blood loss resulting in anemia may produce hypotension, weakness, and loss of balance with heightened risks of transfusion-related lung injury, immune sensitization, disease transmission, and thromboembolism. [12][13][14]30 Although spiral computed tomography allows for direct visualization of pulmonary vasculature to detect compounding PE reliably with a high specificity of 81 to 100%, 31 the routine use of prolonged anticoagulation may lead to unnecessary treatment of isolated subsegmental clots with morbidity. At our institution, the common symptoms of tachycardia, shortness of breath, and a low O 2 saturation (<90%)together with a history of PE/DVT and a BMI of >30 kg/m 2 were associated with a positive detection of life-threatening events.…”
Section: Discussionmentioning
confidence: 99%
“…29 Blood loss resulting in anemia may produce hypotension, weakness, and loss of balance with heightened risks of transfusion-related lung injury, immune sensitization, disease transmission, and thromboembolism. [12][13][14]30 Although spiral computed tomography allows for direct visualization of pulmonary vasculature to detect compounding PE reliably with a high specificity of 81 to 100%, 31 the routine use of prolonged anticoagulation may lead to unnecessary treatment of isolated subsegmental clots with morbidity. At our institution, the common symptoms of tachycardia, shortness of breath, and a low O 2 saturation (<90%)together with a history of PE/DVT and a BMI of >30 kg/m 2 were associated with a positive detection of life-threatening events.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 695 patients, Kim et al 7 found a 27.8% rate of positive computed tomographic pulmonary angiography (CTPA) results for PE in postoperative orthopaedic patients. It often is subtle, atypical, or even silent.…”
Section: Diagnosismentioning
confidence: 99%
“…As such, the implementation of effective prophylaxis against DVT assumes paramount importance in mitigating the risk of VTE complications. A multitude of guidelines and recommendations have been established to assist clinicians in selecting the most appropriate prophylactic approach, accounting for factors such as individual patient risk, the nature of the surgical procedure, and other pertinent clinical considerations [ 14 ]. Among these recommendations, the American College of Chest Physicians advises the use of mechanical prophylaxis methods, including graduated compression stockings (GCS), intermittent pneumatic compression (IPC), or a combination of mechanical and pharmacological approaches for patients at high risk of DVT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%